2015
DOI: 10.1080/10286632.2015.1128418
|View full text |Cite
|
Sign up to set email alerts
|

The ecologies and economy of cultural value from research

Abstract: This study explored conceptually and empirically the ways in which those engaged with university-based arts and humanities research (researchers, managers, partners, beneficiaries) construct and respond to the challenges of generating, interpreting, and demonstrating the cultural value of research. Cultural value is a contested concept, beset by philosophical, practical and political tensions. We argue that interpretations of valuecultural or otherwiseare part of complex ecologies of cultural life, creation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The concept of value and valuing certain 'goods' like knowledge (epistemic value), was prominent throughout the interviews. Some suggested a hierarchy of value, where instrumental (e.g., economic and commercial) value was in some way "better", or at least easier to measure, than cultural and social value (Oancea et al, 2015. There was a recurrent observation that those conducting non-instrumental research felt the need to defend their more nuanced forms of impact and appeared to be unsure as to what constituted 'enough' impact.…”
Section: Contrasting Views On Impact and The Value Of Knowledgementioning
confidence: 99%
“…The concept of value and valuing certain 'goods' like knowledge (epistemic value), was prominent throughout the interviews. Some suggested a hierarchy of value, where instrumental (e.g., economic and commercial) value was in some way "better", or at least easier to measure, than cultural and social value (Oancea et al, 2015. There was a recurrent observation that those conducting non-instrumental research felt the need to defend their more nuanced forms of impact and appeared to be unsure as to what constituted 'enough' impact.…”
Section: Contrasting Views On Impact and The Value Of Knowledgementioning
confidence: 99%
“…The studies that provided the empirical background for this paper were funded by several grants from the Arts and Humanities Research Council; HEIF; British Educational Research Association; and the University of Oxford. Some parts of the text are adapted with permission from Oancea (2015) and Oancea (2016).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The grounds for this selection are both a priori, as themes identified through conceptual and theoretical inquiry into the notions of research quality, performance and value/ evaluation; and a posteriori, as categories developed from empirical studies of RAE and REF submission data and of interview and survey data spanning four national exercises: RAE 1996, 2001, and REF 2014. While the theoretical arguments and the findings of these studies are reported elsewhere (e.g., Oancea, 2008Oancea, , 2010Oancea, , 2014Oancea et al, 2018), this paper attempts to draw them together reflectively in an exploration of ongoing trends and discursive threads underpinning recent public debates around research assessment and its future in the UK and beyond.…”
mentioning
confidence: 98%
See 2 more Smart Citations